Effective factors on increasing students' sense of belonging in the design of student dormitories using biophilic architecture approach - Sima Abyazi; Mojtaba Pourahmadi (مهندسی و مدیریت ساخت, 2021)
Many students are forced to leave their place of residence to study and choose student dormitories to stay. The current research examines the architectural design of student dormitories from a biophilic perspective, and its purpose is to improve the sense of belonging and comfort of students in the dormitories. Upon entering the dormitory, students face feelings such as homelessness, loneliness, anxiety and depression, and they do not feel attached to the new place. The lack of a sense of belonging to the dormitory in the students and the disruption of their peace can lead to the academic decline of the students. Therefore, it is necessary to analyze and investigate the architecture of student dormitories from the point of view of influencing the sense of belonging and peace of students. Considering the students' need for a sense of belonging and peace, using biophilic architecture as one of the trends of sustainable architecture is a way forward. Biophilic architecture tries to understand the inherent needs of humans and their connection with the natural environment and tries to evolve human-nature relations in order to create peace, comfort and a sense of belonging in humans. Biophilic design reinforces our emotional attachments to places. This design approach creates emotional attachment to places in humans and creates the concept of belonging. In this research, the factors affecting students' comfort and sense of belonging in the dormitory are investigated using biophilic design solutions, including the presence of natural environment, and models are presented using biophilic design to create a sense of belonging in the student dormitory.